Bilanggays - Singh, Rodemille Guadalupe (2014)
"Bilanggays is a film that talks about the current state of the LGBT community in the Philippines and how, specifically the bakla, is prisoned by the intricacies of religion and by the society they live in. It exposes how society hinders the freedom of the LGBT community by enclosing them to stereotypes - paralleled to the "Bilanggays" who are being enclosed to the prison. The film aims to deconstruct the stereotypes that limit the identity and the concept of the "bakla" by contesting the different ideologies and assumptions about it. The film will show how the bakla empower themselves by creating their own space of liberty. Bilanggays aims its audience to realize that the struggles of the bakla is similar to imprisonment - "katulad lang din ng mga preso, yun nga lang ang lipunan ang nagkulong sayo."